Effects of precursor concentrations on the optical and morphological properties of ZnO nanorods on glass substrate for UV photodetector. (November 2017) - Abuelsamen, A.A.; Mahmud, Shahrom; Seeni, Azman; Kaus, Noor Haida Mohd; Farhat, O.F.
Abstract: In this study, zinc oxide (ZnO) nanorod arrays with various precursor concentrations (0.05, 0.10 and 0.15 M) were synthesized using a simple hydrothermal reaction on ZnO seeds/glass substrate and tested for UV-photodetector. The structural and optical properties of the ZnO nanorods have been investigated. The results demonstrate that morphology and crystallinity of ZnO nanorods influenced by the concentration of the precursor and had a high impact on the UV-photosensing. As the precursor concentration increased by 0.1 M, the density and the surface-to-volume ratio of ZnO nanorods decreased by 49 nanorods per μm 2 and 22.9 respectively. At the lowest concentration of 0.05 M, the ZnO nanorods grew with high density of 85 nanorod per μm 2 and high surface-to-volume ratio of 28.5. Moreover, a strong ultraviolet (UV) emission peak (λ = 375 nm) was observed with a low deep-level emission peak (λ = 580 nm), which indicated high optical property and crystallinity of the nanorods. The synthesized ZnO nanorods exhibited different sensing characteristics that correlated with the morphological and structure of ZnO nanorods formed at different concentrations. The sample grew with concentration of 0.05 M showed the highest photocurrent of 1.949 × 10 −4 A and current gain of 562.1 under low power intensity UV illumination at λ = 375 nm with 5 V bias. Highlights: ZnO nanorods with various precursor concentrations were synthesized on glass substrate and tested for UV-photodetector. Different precursor concentrations impacted the morphology, density, crystallinity and optical properties of ZnO nanorods. The highest current gain of 562.1 was obtained for ZnO nanorods synthesized using the concentration of 0.05 M.